1989
DOI: 10.3382/ps.0680153
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Levels and General Performance of Commercial Broilers Fed Practical Levels of Redfish Meal

Abstract: A total of 1,200 day-old Arbor Acre broiler chickens was randomly assigned to 12 pens (50 males and 50 females/pen) and divided into three blocks of four pens each. Each of four different diets was fed ad libitum to one pen of birds within each block to determine the effect of feeding practical levels of redfish meal (RFM) on performance and omega-3 fatty acid content of edible meat and skin lipids of broiler chickens. The four diets included (control) 0%, 4.0%, 8.0%, and 12.0% RFM. Feeding diets containing RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
3
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 20 publications
10
40
3
4
Order By: Relevance
“…The poultry industry has made significant efforts to decrease the total amount of abdominal fat deposited in broiler chickens through genetics, management and nutrition. Studies in poultry nutrition have shown that the fatty acid profile of poultry meat can be modulated by dietary outcome (Hulan et al, 1989;Fébel et al, 2008;Ponte et al, 2008). Previous studies focused mainly on the fatty acid profile of meat (dietary outcome) rather than the mechanisms through which dietary manipulations change lipid deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The poultry industry has made significant efforts to decrease the total amount of abdominal fat deposited in broiler chickens through genetics, management and nutrition. Studies in poultry nutrition have shown that the fatty acid profile of poultry meat can be modulated by dietary outcome (Hulan et al, 1989;Fébel et al, 2008;Ponte et al, 2008). Previous studies focused mainly on the fatty acid profile of meat (dietary outcome) rather than the mechanisms through which dietary manipulations change lipid deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Ajuyah et al (1991) showed that the use of linseed oil or whole linseed in poultry diets resulted in tissue enrichment of n-3 PUFA (C20:5n-3 and C22:6n-3) derived from C18:3n-3 by desaturation and elongation. Hulan et al (1989) indicated that marine oils and fish meal containing residual lipid increased the C20 and C22 n-3 PUFA concentration of poultry tissue.…”
Section: Introductionmentioning
confidence: 99%
“…E esse renovado e crescente interesse continua pelos mesmos motivos já previamente citados, a promoção da saúde humana através da redução de doenças cardíacas da coronária (Leaf and Weber, 1988) e tratamento de doenças inflamatórias como artrite reumatoide (Barlow and Pike, 1991). Hulan et al (1989) relataram que uma porção de 100 g de carne de frango previamente alimentados com uma dieta contendo 12% de farinha de peixe marinho contribuiriam com aproximadamente 197 mg de ômega 3 para o consumo médio diário, como comparado aos 138 mg fornecidos por uma porção equivalente de peixe branco. Uma dieta menos enriquecida chega a conter uma média de 1.7 g de ômega 3 diários, dos quais 90 % é ácido linolênico (Barlow and Pike, 1991).…”
Section: Enriquecimento Da Carne De Ave Com ôMegaunclassified
“…Miller and Robisch (1969) ao avaliarem os efeitos da suplementação com 2.5% e 5% de óleo de peixes marinhos durante 4, 5, 6 e 8 semanas sobre a deposição de ômega 3 na carne, encontraram que a deposição de ômega 3 aumenta conforme a duração do enriquecimento na dieta. Outros estudos também observaram diferenças na deposição de ômega 3 nos tecidos (Hulan et al, 1989, Hulan et al, 1988, Huang et al, 1990, sendo que a observação de deposição preferencial de ácidos graxos ômega 3 na carne, particularmente na carne do peito das aves, podem proporcionar benefícios econômicos, pois o a indústria e o consumidor podem remunerar a produção e comércio desses produtos (Wiseman, 1990).…”
Section: Enriquecimento Da Carne De Ave Com ôMegaunclassified